Responsabilidade social corporativa e direitos humanos: discursos e realidades - MATHIS, Adriana de Azevedo (Universidade Federal do Pará, 2018)
This article conducts a critical analysis of the creation and consolidation of global parameters for Corporate Social Responsibility (CSR) in relation to human rights in Europe and Brazil, in the current stage of globalized capitalism. As a methodological-theoretical resource, it is based, on the international level, on a set of legal norms about corporate social responsibility and human rights at transnational companies. On a national level, the study uses as a theoretical-methodological reference a bibliographic survey of the concept of CSR in new standards of peripheral capitalism, inserted in the context of globalization.